A formação do enfermeiro para o cuidado à saúde da criança e do adolescente na graduação em enfermagem na Região Oeste do Paraná - Jorge, Kelly Jackelini (2013)
Professional training may contribute to the consolidation of the Unified Health System, especially training to the care integrality. Exploratory and descriptive study, generally aiming to investigate the nurse s training to care the Child and the Adolescent in nursing graduation courses in the Western Region of Paraná State. With specific goals: to analyze the scientific publishing to the nurse s training to Healthcare to the Child and Adolescent in Brazil, by means of an integrative review, to identify the dimension assumed by the nursing care in Child and Adolescent s health inside the politic and pedagogic projects and teaching plans of nursing graduation courses within the Western Paraná Region. To investigate the relationship established between the training to healthcare to Child and Adolescent in the Unified Health System, specially to what refers to the integrality principle, to identify in the Professor s Speech of the studied courses how it materializes the healthcare teaching to Child and Adolescent from the implementation of the Unified Health System and of the National Curricular Directives indications to the graduation course in nursing. There was carried out the Integrative Review, research of documental data and semi structured interview with the Professors responsible for the disciplines reserved for teaching the healthcare to Child and Adolescent. The integrative review indicated the pertinence of the integrality basing the training to healthcare to Child and Adolescent; the regard to the family and; the process learning-teaching with their elements composing the formation to health of Child and Adolescent. The documental data analysis and the interviews resulted in the following themes: pedagogical political projects and teaching plans; the materiality of the discourses about formation; the subjects and their involvement with the institutional reality; integrality in the training to the care of the nurse to healthcare of Child and Adolescent. They indicated that to the formation to the Unified Health System it must be proportioned effective living of the system. Since their first terms of training with equivalent workload between the theoretical and practical activities; the courses incorporate a theoretical outline and a speech of integrate formation; the professors exposed an approximation with a training to the Unified Health System internalizing concepts as promotion, protection, prevention, integrality and broad training. However, some effective proposes are distant to what is a solid training to that system, explicitly in the distancing of pedagogical actions in fields of practice immerging after the Curricular Directives. The integrality weakens in the training due to its absence in health services; by its precariousness of the practice field and by the lack of effective politics to solving the care to Child and Adolescent.